The Challenge and Opportunity to Diagnose Parkinson's Disease in Midlife - Kilzheimer, Alexander; Hentrich, Thomas; Burkhardt, Simone; Schulze-Hentrich, Julia M. (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder that affects extensive regions of the nervous system. Its current clinical diagnosis is based on motor symptoms that appear late during disease progression when substantial proportions of the nigrostriatal dopaminergic neuron population are lost already. Although disturbances in sleep and other biofunctions often surface years prior to motor impairments and point to a long prodromal phase, these phenotypic signs in a person’s midlife lack predictive power. They do, however, signal the unfolding of the disease and suggest molecular correlates that begin deviating early on. Revealing such trajectories, hence, promises not only a better understanding of prodromal PD but may also enable a much-needed earlier diagnosis. A central nexus that promises to harbor such molecular trajectories is the epigenome because key etiological factors of PD—genetics, age, and environment—influence this substrate. An earlier diagnosis would also allow earlier interventions and lifestyle adjustments to improve brain function and reduce symptoms. In this review, we describe the challenges of diagnosing PD early on and highlight the opportunities that may arise from steering research efforts towards comprehensive interrogations of molecular layers during the long-time neglected midlife phase. In particular, we emphasize how existing cohorts of at-risk individuals, available animal models, and suitable markers may come together and aid in revealing molecular trajectories that offer diagnostic utility for PD in its prodromal stage.